The impact mechanism of human activities on the evolution of coastal wetlands in the Liaohe River Delta - Deng, Qinghai; Zhang, Xinming; Zhang, Liping; Shao, Xin; Gu, Tianshuo (Frontiers in Ecology and Evolution, 2024)
IntroductionThis study aims to investigate the impact of human activities on the evolution of coastal wetlands in the Liaohe River Delta. Understanding these impacts is crucial for the management, protection, and sustainable development of the ecological environment in the region.MethodsQuantitative analysis of the evolution of coastal wetlands along the Liaohe River from 1995 to 2020 using Landsat series remote sensing images. This study examines the changes in different landscapes and explores the impact of human activities on wetlands through methods such as land transfer matrix, landscape pattern index, and human activity hotspots.ResultsThe results show that the area of coastal wetlands in the Liaohe River Delta exhibited a fluctuating downward trend from 1995 to 2020. The eastern and western parts of the delta experienced greater disturbance to wetland landscapes due to human activities, while the northern and southern parts were mostly waters and reed lands with a smaller degree of human disturbance. Human activities have led to significant changes in farmland, ponds, rice paddies, construction land, and reed fields, thereby promoting the evolution of coastal wetlands.DiscussionThis article discusses the characteristics of landscape pattern evolution in the study area, as well as the impact of human interference, economy, policies, and other factors on it, and compares it with the evolution patterns of other coastal wetlands in China. The changes in the landscape pattern of the study area are mainly reflected in the reduction and fragmentation of natural wetland areas, which are closely related to human activities, especially the development of construction and agriculture. The main economic manifestation is that the increase in land demand due to economic and urban development has led to the transformation of natural wetlands into construction land and other artificial landscapes. The implementation of regulations such as the Wetland Protection Law has contributed to the rational use and ecological restoration of wetlands, and also reflects the influence of policy factors. Compared with other studies, coastal wetlands in China generally face issues of degradation and loss, mainly caused by human activities, but also affected by natural factors such as rising sea levels, changes in coastlines, and climate change.